The Description of Parents Knowledge Level in Teaching Sex Education to Preschool Age Children in Banjar Kertagraha Kesiman Kertalangu Denpasar - Dewi, Luh Putu Diah Kusuma; Prihatiningsih, Diah; Laksmi, I Gusti Ayu Putu Satya (Future Science, 2022)
Early childhood sex education is teaching, awareness, and enlightenment to children about sex problems since they think about sexual problems. The initial stage of sex education is teaching the concept of right and wrong, getting used to cleaning the body, teaching how to take care of yourself, and how to build relationship with other people so that children do not have wrong understandings and fall into acts of violence and as a prevention of sexual violence. The purpose of this study was to describe the knowledge of parents about the learning process of sex education in pre-school age children in Banjar Kertagraha, Kesiman Kertalangu Village, Denpasar, Bali. This research uses a descriptive method. This study uses a total sampling technique. The number of respondents is 63 people. The location of this research is in Banjar Kertagraha, Kesiman Kertalangu Village, Denpasar, Bali. This research was conducted on 12-19 November 2021. The research instrument used a questionnaire with univariate data analysis technique. The results showed that the level of parental knowledge about sex education for preschool children in Banjar Kertagraha, Kesiman Kertalangu Village, Denpasar Bali, generally found that most of the parents who have sufficient knowledge are 33 respondents (52.4%), and those who have good and low knowledge are 18 respondents (28.6%) and 12 respondents (19%). For further researchers to carry out broader research related to parental knowledge in teaching sex education to preschool age children.